Branding Waqf for Sustainable Development: A Marketing Approach - Abdullahi, Shafiu Ibrahim (International Journal of Economics, Management and Accounting, 2022)
Recent years have seen discussions on the need to develop the managerial architecture of waqf to align it with modern realities. Awqaf are suffering from a lack of funds to run their activities. The image of some awqaf has been damaged by poor performance, historical neglect, and colonial past. Efforts at redeveloping waqf must not neglect organizational image building. To achieve this, the use of modern marketing and communication tools is inevitable. The focus of this paper, therefore, is not on defining waqf or describing its functions but on creating a good image of waqf in the public mind. The role of organization’s image in the public mind in helping the organization achieve its mission has long been recognized by marketing and communication scholars. Hence the research method followed for this work is an intensive study of selected literature and a critical analysis of their contents. The work also benefits from careful study of existing awqaf operations. Thus, this work is conceptual in nature. It is observed that waqf shall provide the needed resources for dealing with long-term challenges that require painstaking efforts going beyond political winds and short-term business interests. These include supporting efforts at tackling environmental challenges such as afforestation campaigns and green financing.